Desvendando a Ligação da Frutose e da Glicose à Albumina do Soro Humano: medições de fluorescência e cálculos de docking, dinâmica molecular e bioquímica quântica - Cortez, André Hadad (2024)
This research examines the interaction between human serum albumin (HSA) and various sugar forms (β-D-fructofuranose (FRC), α-D-glucopyranose (GLC), Keto-D fructose (FRO), Aldehydo-D-glicose (GLO), and hexane-1,2,3,4,5-pentol modified D glicose (GLOm)) using fluorescent spectroscopy, molecular docking simulations, molecular dynamics, protein conformational clusters (EnGens), molecular fractionation with conjugate caps (MFCC) and quantum biochemistry analysis. We analyze molecular and quantum aspects, uncovering interaction energies between sugar atoms and amino acids. Total interaction energy considers protein fragmentation, energetic decomposition, and interaction energy from a bottom-up perspective. Molecular dynamics reveal that unmodified Aldehydo-D-glicose (GLO) escapes HSA binding sites, explaining gradual glycation. We pioneer studying HSA's binding mechanism with glicose and fructose in a 1:1 ratio using long molecular dynamics simulations. Results suggest the ransitional GLOm form has a higher Sudlow site I propensity than unmodified glicose, crucial for LYS195 glycation. FRO and GLOm interaction tendencies move toward a deeper FA7 cavity, near its center. This approach effectively elucidates small molecule binding mechanisms, consistent with previous experimental results.